The six-minute walk test predicts cardiorespiratory fitness in individuals with aneurysmal subarachnoid hemorrhage. Issue 4 (19th May 2017) - Harmsen, Wouter J.; Ribbers, Gerard M.; Slaman, Jorrit; Heijenbrok-Kal, Majanka H.; Khajeh, Ladbon; van Kooten, Fop; Neggers, Sebastiaan J. C. M. M.; van den Berg-Emons, Rita J.
Abstract: Background: Peak oxygen uptake (VO2peak ) established during progressive cardiopulmonary exercise testing (CPET) is the "gold-standard" for cardiorespiratory fitness. However, CPET measurements may be limited in patients with aneurysmal subarachnoid hemorrhage (a-SAH) by disease-related complaints, such as cardiovascular health-risks or anxiety. Furthermore, CPET with gas-exchange analyses require specialized knowledge and infrastructure with limited availability in most rehabilitation facilities. Objectives : To determine whether an easy-to-administer six-minute walk test (6MWT) is a valid clinical alternative to progressive CPET in order to predict VO2peak in individuals with a-SAH. Methods: Twenty-seven patients performed the 6MWT and CPET with gas-exchange analyses on a cycle ergometer. Univariate and multivariate regression models were made to investigate the predictability of VO2peak from the six-minute walk distance (6MWD). Results: Univariate regression showed that the 6MWD was strongly related to VO2peak ( r  = 0.75, p  < 0.001), with an explained variance of 56% and a prediction error of 4.12 ml/kg/min, representing 18% of mean VO2peak . Adding age and sex to an extended multivariate regression model improved this relationship ( r  = 0.82, p  < 0.001), with an explained variance of 67% and a prediction error of 3.67 ml/kg/min corresponding to 16% of mean VO2peak . Conclusions: The 6MWT is an easy-to-administer submaximal exercise test that can be selected to estimate cardiorespiratory fitness at an aggregated level, in groups of patients with a-SAH, which may help to evaluate interventions in a clinical or research setting. However, the relatively large prediction error does not allow for an accurate prediction in individual patients. Abstract :